Exodus from Cardiganshire : Rural-Urban Migration in Victorian Britain. - Cooper, Kathryn J. (Studies in Welsh history., 2011)
Was migration from Victorian Cardiganshire simply a flight from rural poverty? This book relates the rate and timing of the outward movements from the county in the nineteenth century to the prevailing social and economic conditions. It provides insights into the motivations for and factors involved in migration; and using contemporary source material and computer-assisted analysis of census enumerators' books examines key dimensions of the communities at the major migrant destinations - Glamorgan, Carmarthenshire, London and Merseyside in Britain, and Ohio and Wisconsin, USA.